Implementasi program takhassus tahfidz Al-Quran di pondok pesantren Nurul Islam Pungging Mojokerto - Nafiah, Maftukatun; Zaini, Abdullah (Program Studi Pendidikan Agama Islam STAI Auliaurrasyidin Tembilahan, 2024)
In the modern era, Qur'anic character among individuals, particularly teenagers, is gradually fading due to the influence of free association. This study aims to describe the teaching methods and the supporting and inhibiting factors of the Takhassus Tahfidz Al-Qur'an Program at Pondok Pesantren Nurul Islam Mojokerto. The research employs a qualitative descriptive approach with a field research method. Data were collected through observation, documentation, and interviews, and analyzed using an interactive model, including data reduction, data presentation, and conclusion drawing. The results of the study show that the Takhassus Tahfidz Al-Qur'an Program at this pesantren uses the ziyadah and tasmi’ methods. The supporting factors include (1) the consistency of both teachers and students, and (2) full support from the formal educational institution within the pesantren. The inhibiting factors are (1) students’ lack of awareness about the importance of their chosen program, (2) students' inability to manage their time effectively, and (3) insufficient rest, leading to drowsiness.